Grandparent support of mothers caring for a child with a disability: Impacts for maternal mental health. (May 2018) - Crettenden, Angela; Lam, Joey; Denson, Linley
Abstract: Background and aims: Mothers who are primary carers of children with disabilities experience more mental health problems than mothers of typically developing children. We aimed to update and extend research into mothers' perceptions of grandparent support with care, and impacts for maternal psychological well-being, because although contemporary grandparents live longer they also work longer. Methods: Surveys were completed by 72 mothers of clients (aged ≤8 years) of an Australian non-government disability agency. Mothers reported levels of practical and emotional support, face-to-face contact, and affectional solidarity with maternal and paternal grandparents. The Kessler Psychological Distress Scale (K10) was the dependent variable. Results: Mothers indicated high to very high levels of psychological distress. As in previous comparable surveys, most support was offered by maternal grandmothers who had more contact and closest relationships with mothers. Maternal distress was related to maternal grandmothers' health and relationships with maternal grandfathers. Face-to-face contact and closeness of relationships were strongly linked to provision of support. Conclusions and implications: Grandparents are important supports for mothers of children with disabilities: mothers lacking support from their own parents are particularly vulnerable. Clinicians should actively facilitate grandparent involvement, and promote extended family relationships.